(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
One of the most critical concerns of our generation is sustainability. This study aims to determine the extent to which the construction sector in Nepal considers and applies sustainability concepts in its project management activities to develop a change strategy to improve sustainability practices. To better understand the existing situation, this research was conducted through semi-structured interviews. First, the existing literature on sustainability practices was critically studied to understand the current situation and the participating company’s objective to improve sustainability performance in developing countries. The literature review results formed the basis for a series of semi structured interviews with eight members of middle and senior management representing three different stakeholder groups: clients, contractors, and regulatory agencies. The interviews were conducted to gain a deeper understanding of the reasons behind current practices and barriers to implementing sustainability in Nepalese mixed-use buildings. The interview data were coded and analyzed using the thematic analysis method. The findings of this research show how difficult it is to implement sustainability in buildings of Nepal, and the statistics show that the practices of many organizations are poor in terms of socio-environmental sustainability.